Manual on the creation of quality indicators for population based cancer screening programs in Italy. (30th September 2020) - Rivolta, S; Ponti, A; Deandrea, S; Campari, C; Zorzi, M; Zappa, M; ,
Abstract: Issue: In many countries the organized screening programs have been in the frontline in developing and implementing the evaluation of the quality of screening and of the entire process of care following a positive test. Over the years, the three Italian Screening Groups (GIS) have separately published indicators and standards concerning the programs for breast, cervical and colorectal cancers they were responsible for, thus hampering coherence, homogeneity. In addition, at local level, an increasing number of indicators have been observed with difficult to monitor all of them. Description of the Problem: The Screening Indicators Manual, prepared by a multidisciplinary working group, represents the guidance agreed upon by the Italian Screening Network (ONS) and the three GIS on how to develop, implement, communicate and maintain a set of quality indicators for the evaluation of cancer screening programs. Results: The Manual indicates that the three GIS must first constitute, with ONS, the common steering committee made of six-nine experts. The involvement of the public and the management of the conflicts of interests are foreseen. The conceptual framework distinguishes indicators of context, coverage and process. It is based on six dimensions: efficacy, efficiency, security, appropriateness, person centeredness, equity. There are four macro-processes: invitation; test, further assessment and diagnosis; treatment and follow-up; evaluation. The methods include: a survey of the existent indicators, their selection with the Delphi method, the evaluation of the completeness of the resulting indicators set, its integration, when needed, by means of a public call, and finally a new Delphi round. Appropriate standards, empirical or evidence based, are then identified. Last, indicators are assigned to core or library list based on priority. Lessons: Select, define and measure an indicator is a way to understand what we are aiming at even more than provide the measure of how we do it. Key messages: The creation of the Manual allows to build a coherent evaluation framework for the three screening programs. The Manual promotes the adoption of rigorous methods and make feasible the monitoring activity according to its purpose, level of observation and detail of information needed.